The The The Influence Of Sharia Compliance And Institutional Ownership On Sustainability Report Disclosure At The Jakarta Islamic Index 2021-2023 - Anwar, Azwar (International Economic Conference of Business and Accounting, 2024)
The aim of this research is to analyze the influence of sharia compliance on sustainability disclosure report on companies listed on the Jakarta Islamic Index 30 (JII 30). The samples from this research consisted of 21 companies selected using the purposive sampling method . The results of this research indicate that Sharia Compliance in the form of the ratio of interest debt to assets has a significant negative effect on Sustainability Disclosures Reports or the ratio of interest-bearing debt to total assets are inversely proportional to encouraging sustainability disclosure report of a company. The other Sharia Compliance variable (non-halal income to total income), has no significant partial effect, nor does the Institutional Ownership variable has a partial effect on Sustainability Disclosure. Report. Simultaneously, the Ratio of Interest-Bearing Debt to Total Assets, the Ratio of Non-Halal Income to Total Income and Institutional Ownership have a significant effect on Sustainability Reports.